Potential Effect of Black Cumin Honey on Skin Wrinkles, Pores, Moisture, and Sebum - Girsang, Helen Pratiwi P.; Handoko, Erwin; Ginting, Chrismis Novalinda; Ginting, Sahna Ferdinand; Ikhtiari, Refi (European Journal of Applied Sciences, 2022)
Acne vulgaris is a chronic inflammation of the polysebaceous follicles with the presence of blackheads, papules, pustules, and cysts in predilection areas. The new drug development to provide more effective therapy of topical cream containing bioactive compounds has emerged. The properties possessed by black cumin and honey can be combined as a new anti-acne drug. This research aims to provide the skin evaluation data of modified topical cream of black cumin honey by following the guidelines of good manufacturing practice (GGMP). The organoleptic, pH, homogeneity, scatter power, cream type, and stability of combination cream have been tested. The the effectiveness of cream was evaluated based on the number of skin wrinkles, skin moisture content, number of skin pores, and sebum. Results showed that a combination cream of 5% extract has met the good standard of preparation. The topical application involving 40 volunteers within two weeks showed a significant effect on increasing the skin moisture and also reducing the skin wrinkles, pores, and sebum. This research showed the black cumin honey cream could improve skin conditions and potentially be used for topical antiacne treatment soon.